Визначення точності геодезичних робіт при монтажі мостових переходів на основі теорії розмірних ланцюгів - Адаменко, Олександр (Видавництво Національного університету «Львівська політехніка», 2009)
The article contains the information about new principles of accuracy surveing in geodetic engineering in the course of bridge crossings building on the basis of dimension chain theory.
Keywords: bridge; dimension chain theory; accuracy surveing in geodetic engineering; жорсткість